Two-Dimensional Nanostrips of Hydrophobic Copper Tetradecanoate for Making Self-Cleaning Glasses. (24th March 2016) - Sarkar, Subhrangsu; Mukherjee, Indrani; Chatterjee, Sriparna; Gohil, Smita; Singh, Bimal P.; Ayyub, Pushan
Abstract : We report a simple, solution-based technique for coating arbitrary surfaces with thin layers of self-assembled copper tetradecanoate (CTD) nanostrips, resulting in an optically transparent, superhydrophobic coating. The nanostrip-coated surfaces show water contact angles close to 150° and roll-off angles as small as 2°-3°. Importantly, CTD retains its hydrophobic nature even after annealing the self-assembled nanostrips at 200°C, which does not alter the crystal structure but "melts" the surface microstructure. This clearly indicates that the hydrophobicity in CTD is likely to be intrinsic in nature and not induced by the surface microstructure (as has been suggested earlier). Strong hydrophobicity in CTD over a relatively wide temperature range presumably results from the presence of the long aliphatic (tetradecanoate) chains in its structure. Importantly, the self-assembled copper tetradecanoate nanostrips can be dip-coated on glass to render it hydrophobic and at the same time retain a significant level of transparency over the entire visible region. Such nanostructured thin films may be expected to find applications not only as a self-cleaning glass, but also as a corrosion resistant coating, in gas storage (due to the layered structure), and as an active catalyst because of the visible absorbance.